Digital communication and NextGenerationEU european funds: analysis of the web portals of spanish administrations - Vilaplana-Aparicio, María J. (2025)
The communication-public aid binomial is becoming more decisive because the funds provided by the EU are linked to the obligation on the part of the managing administrations to carry out effective social communication.  For the first time, Europe has agreed to issue public debt to deal with the consequences created by Covid-19. To this end, it has created the NextGenerationEU instrument, endowed with €809 billion, with the aim of achieving a more digitalized, sustainable and innovative EU. Among the countries that have benefited the most is Spain, which has given a leading role to its 19 regions (Autonomous Communities and Cities) in channelling and structuring the funds. Likewise, to ensure their proper dissemination, the EU enacted the need for Member States to create a website to act as a one-stop shop. Spain created its own and urged the different regions to do the same. Therefore, this paper explores whether regions have created a website that brings together Next Generation information and measures its quality. For this purpose, a protocol was created consisting of eight parameters and 65 indicators. The Valencian Community, Catalonia and Aragon are the regions with the best performance, while the Canary Islands, Navarre and Ceuta are the most deficient.